Strengthening effect of melamine functionalized low-dimension carbon at fiber reinforced polymer composites and their interlaminar shear behavior. (15th September 2019) - Cha, Jaemin; Kim, Joonhui; Ryu, Seongwoo; Hong, Soon H.
Abstract: The strengthening mechanism of graphene nanoplatelets (GNPs) and carbon nanotubes (CNTs) at general fiber reinforced polymer (FRP) composite were investigated by interlaminar shear failure. We proposed 6 steps of interlaminar shear behavior of laminates at FRPs impregnated with epoxy resins. The GNPs and CNTs were functionalized by melamine to form M-CNTs and M-GNPs, which improved their dispersion in the epoxy matrix of the CFRPs and enhanced the interfacial strength. As a result, the resistance to crack propagation at the interface of fiber and polymer matrix increased. The interlaminar shear deformation behavior was characterized performing an interlaminar shear strength (ILSS) test, and the six failure stages were observed by scanning electron microscopy. Differences between load–displacement curves and the effects of GNPs and CNTs on shear deformation were analyzed. The incorporation of 2 wt% of M-CNTs increased the ILSS value of the CF/M-CNT/epoxy nanocomposite by 61%. The same loading but with M-GNPs increased the ILSS of the CF/M-GNP/epoxy nanocomposite by 219%. The greater reinforcing effect of the M-GNPs than the M-CNTs was attributed to differences in delamination resistance at the interface between the fibers and the epoxy. The phenomenon of crack propagation was investigated and related to the improved ILSS values.